2012
DOI: 10.1109/jlt.2012.2187879
|View full text |Cite
|
Sign up to set email alerts
|

Photonic Generation of Phase-Modulated RF Signals for Pulse Compression Techniques in Coherent Radars

Abstract: A novel and flexible photonics-based scheme is proposed for generating phase-coded RF pulses suitable for coherent radar systems with pulse compression techniques. After selecting two modes from a mode-locked laser (MLL), the technique exploits an optical in-phase/quadrature modulator driven by a low-sample rate and low-noise direct digital synthesizer to modulate the phase of only one mode. The two laser modes are then heterodyned in a photodiode, and the RF pulse is properly filtered out. The scheme is exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
44
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(44 citation statements)
references
References 20 publications
0
44
0
Order By: Relevance
“…Previously various photonic techniques to generate pulsed microwave signals have been demonstrated including a four-tap photonic microwave delay-line filter [2], phase modulation [3,4], polarization modulation [5] and a modelocked laser and optical filter [6,7]. One of the key components in these systems is a photodiode (PD) that can detect high-power and high-frequency pulsed signals.…”
Section: Introductionmentioning
confidence: 99%
“…Previously various photonic techniques to generate pulsed microwave signals have been demonstrated including a four-tap photonic microwave delay-line filter [2], phase modulation [3,4], polarization modulation [5] and a modelocked laser and optical filter [6,7]. One of the key components in these systems is a photodiode (PD) that can detect high-power and high-frequency pulsed signals.…”
Section: Introductionmentioning
confidence: 99%
“…The limitation associated with this method is that the generated microwave signal is hardly reconfigurable. On the other hand, optical heterodyning has been proposed to generate phase-modulated microwave signal [5][6][7]. By heterodyning two optical carriers in the PD, the microwave signal with a frequency corresponding to the frequency interval of the two optical carriers is generated.…”
Section: Introductionmentioning
confidence: 99%
“…If the phase of one of the optical carriers is modulated, a phase-modulated microwave signal can therefore be generated. The two optical carriers can be separated using a Mach-Zehnder structure [5] or a Sagnac loop [6], while one of the optical carriers is phase modulated using a phase modulator. However, they suffer from the stability problem because both structures are sensitive to the environmental fluctuations.…”
Section: Introductionmentioning
confidence: 99%
“…Again, the microwave carrier frequency was restricted by the bandwidth and the roll-off performance of the optical filter [8], [9] or the FBG [10]. P. Ghelfi et al reported a phase-modulated RF signal generation technique using a mode-locked laser, an optical in-phase/quadrature modulator, and an optical filter [11]. This method is able to generate binary phase-coded microwave signals and frequency chirped microwave signals.…”
mentioning
confidence: 99%
“…However, the amplitude of the electrical driving signal should accurately be V π , namely the half-wave voltage of the modulator, to ensure a π phase shift of the microwave signal, which reduce the reliability and stability of the system. The methods reported in [5]- [8], [10], [11] also suffer from this problem. Moreover, the use of multiple modulators [8]- [10], [12] increases of the complexity of the system.…”
mentioning
confidence: 99%